Risk Factor The Happening Of Primary Hypertension In Countryside Of Atep Oki Of Subdistrict East Lembean Of Minahasa Regency - Priscillia Merylin Saluy (Klabat Journal of Nursing, 2019)
The purpose of this research is to know the relationship of primary hypertension with the occurrence of risk factors. Design research using a cross sectional with test statistic chi-square. The sample in this research totaled 46 respondents. Results of the study there is no significant relationship between genetic risk factors with primary hypertension with significant value. 403 > 0.05. There is no significant relationship between the risk factors of age with primary hypertension with significant value. 340 > 0.05. There is no significant relationship between the risk factors of smoking with a primary hypertension with significant value. 763 > 0.05. There is no significant relationship between risk factors consume alcohol with primary hypertension with significant value. 235 > 0.05. There is a significant relationship between the risk factors of physical activity/sport with primary hypertension with significant value. 038 < 0.05. There is no significant relationship between risk factors consume saturated fat with primary hypertension with significant value. 856 > 0.05. There is no significant relationship between risk factors consume salt with primary hypertension with significant value. 285 > 0.05. Conclusion of this research only to the lack of risk factors of exercise/physical activity showed a significant relationship against the incidence of hypertension. The recommendations are very important for patients with hypertension or who have not got the disease so doing physical activity/exercise at least 30 minutes each day like jogging or brisk walking in lowering blood pressure or stabilize normal blood pressure.